(untitled) (Research, Society and Development, 2020)
Purpose: to identify the main health demands of students with and without disabilities. Methods: exploratory study, descriptive with schoolchildren with and without disabilities, quantitative approach. The collection data was accomplished out through a structured questionnaire with questions about concept health, be healthy, curiosities in health and sexuality. The data were processed using the Epi Info software. Respected Ethical Aspects. Results: 113 students participated, predominantly female, between 11 and 17 years old. Of these, 10 with disabilities, eight with intellectual disabilities, one with Down syndrome and one with low vision. The themes that arouse more curiosities was: sexually transmitted infections, sexuality and contraceptive methods, alcohol, drugs and obesity. Conclusion: with the health demands found, it is possible to help adolescents with and without disabilities to intervene in their real needs.